Предмет: Математика,
автор: smail520
a)Упростите выражение: 2(m+3)^2-2m^2
б)Найдите его значение при m= -0,25. В ответе запишите полученное число.
Ответы
Автор ответа:
2
2(m+3)^2-2m^2=2((m+3)^2-m^2)=2(m+3-m)(m+3+m)=2+3(2m+3)=6(2m+3)=12m+18
12(-0,25)+18=18-3=15
Ответ:15
12(-0,25)+18=18-3=15
Ответ:15
Похожие вопросы
Предмет: Математика,
автор: svetlana4589
Предмет: Алгебра,
автор: dmitrybborisov
Предмет: Другие предметы,
автор: qa31887
Предмет: Математика,
автор: arturyo
Предмет: Алгебра,
автор: Аноним